Perinatal asphyxia and acute renal failure in neonates: presentation and outcomes - Khan, Azhar A.; Kanth, Anzeen N.; Khan, Aymen M.; Khan, Suhail M.; Wani, Owais A. (International Journal of Contemporary Pediatrics, 2022)
Background: Perinatal asphyxia (PNA) is described by the world health organization as a "failure to begin and sustain breathing at delivery." Acute renal failure (ARF), a well-known consequence of birth asphyxia, has a poor immediate prognosis and can leave survivors with lasting renal impairment. The goal of this study was to find out how often ARF is in cases of PNA and how it relates to the severity of the Apgar score and the grading of hypoxic ischemic encephalopathy. Methods: This study was based on APGAR scores and a renal function evaluation done on day 3 of life on neonates with a gestational age of >34 weeks and signs of birth asphyxia. Results: According to the APGAR score, 46 percent of the 75 infants investigated had mild PNA, whereas 42% and 12% of the babies had moderate and severe PNA. ARF was discovered in 24% of PNA patients, with oliguric renal failure (ORF) in 42% and non-ORF (NORF) in 58%. Blood urea was elevated in all instances with ARF (100%) but only 8% of non-ARF patients. ARF was found in 100% of individuals with severe PNA, but only 28% of patients with mild PNA. ARF was not found in any of the individuals with mild PNA. Only 3 (4%) of asphyxiated babies had abnormal renal USG results. Conclusions: Our findings revealed a substantial link between PNA severity and ARF, with no ARF in mild PNA. The incidence of ARF and the stage of HIE were shown to have a linear association in this study. Only ORF instances resulted in death.